(untitled) (Studia Prawnicze / The Legal Studies, 1967)
Enactments of some scores of conventions on legal assistance concluded between socialist countries give evidence of development trends in the range of a contents and structure of regulations in the law of succession. Although the enactments seem to be much alike they show quite considerable differences in regulating many bequest problems. The differences appear mainly in fundamental prin- ciple approprietness in bequest effecting. From this point of view the agreements on this subject may by divided into two groups. The contracts in which lex patriae of the devisor at the instant of his death is employed for law propriety may be applied to one group, while to the other - the contracts that with regard to the real estate use as a link the place of a property and employs all the features of legis patriae with regard to movable belongings. To the latter belong among others the succession enactments in contracts concluded, by the USSR with other socialist countries. Speaking of details it may be assumed that succession ability is in contracts a subject of fundamental statute of succession. In the case a country is to be a successor, personal property is -due to that country the citizen of which was the devisor at the instant of his death, while real estate falls to the country in the area of which is the possession. Dispositions in case of death are in most contracts sub- jected to the propriety of law of the devisor’s country at the instant of making:a disposition. Some agreements, however, do not provide general regulations in the matter. In such cases the propriety provided in a given contract for all bequest questions involved should be taken also for last will dispositions. In effect, the proprieties with respect to the dispositions in case of death are different in different contracts according to what problems are being regulated in a given contract express,is verbis, and what principle regarding propriety for all bequest problems is to be employed. There may occur, however, the cases in which the propriety of the devisor’s legis patriae established in the mentioned manner is to be excluded. These are the cases in which the disposition of a property in case of death is limited. The establishment of a principle of law propriety is of a great significance also in juridical questions. In many cases in which lex patrliae is taken as a funda- mental principle of a propriety, in the succession procedure the same propriety is applied. On the -other hand, when for real estate a propriety of law is to be employed according to the law respecting the place of the property in question, then the propriety of a court of justice and authorities in this area is also used in the succession procedure. There are of course a number of exceptions from this general tendency due to various considerations of which prevails a tendency to facilitate cooperation and simplify the procedure what is particularly important in jurisdiction. The regulations in the subject are in contracts very extended and in many cases they bring much alike solutions if not quite identical. These are the cases such as for example security of the succession property, opening the last will dis- position, giving out the successed property, share of the consulate and diplomacy officials in the succession processing, etc.